2016
DOI: 10.1056/nejmoa1513614
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Tachycardia Ablation versus Escalation of Antiarrhythmic Drugs

Abstract: In patients with ischemic cardiomyopathy and an ICD who had ventricular tachycardia despite antiarrhythmic drug therapy, there was a significantly lower rate of the composite primary outcome of death, ventricular tachycardia storm, or appropriate ICD shock among patients undergoing catheter ablation than among those receiving an escalation in antiarrhythmic drug therapy. (Funded by the Canadian Institutes of Health Research and others; VANISH ClinicalTrials.gov number, NCT00905853.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
381
1
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 674 publications
(399 citation statements)
references
References 20 publications
5
381
1
12
Order By: Relevance
“…35,36 Sotalol has been shown to reduce ICD shocks among patients who are implanted with ICDs for secondary prevention but has not been demonstrated to be superior to -blocker therapy according to several randomized controlled trials. 27,37,38 CA The role of CA in VT management is becoming increasingly relevant, having repeatedly shown its superiority to medical therapy in reducing the arrhythmic burden and thus improving the prognosis and quality of life for patients with structural heart disease who present with VT. 15,39,40 In the specific setting of ES, CA is effective both in the acute suppression of VAs and the long-term prevention of VT and ES recurrences ( Table 2). 41,42 In a pooled meta-analysis of 471 patients with ES who were treated invasively, the acute elimination of all inducible VAs was achieved in 72% of cases, with clinical arrhythmias effectively suppressed in 91%.…”
Section: Electrical Storm In Icd Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 Sotalol has been shown to reduce ICD shocks among patients who are implanted with ICDs for secondary prevention but has not been demonstrated to be superior to -blocker therapy according to several randomized controlled trials. 27,37,38 CA The role of CA in VT management is becoming increasingly relevant, having repeatedly shown its superiority to medical therapy in reducing the arrhythmic burden and thus improving the prognosis and quality of life for patients with structural heart disease who present with VT. 15,39,40 In the specific setting of ES, CA is effective both in the acute suppression of VAs and the long-term prevention of VT and ES recurrences ( Table 2). 41,42 In a pooled meta-analysis of 471 patients with ES who were treated invasively, the acute elimination of all inducible VAs was achieved in 72% of cases, with clinical arrhythmias effectively suppressed in 91%.…”
Section: Electrical Storm In Icd Patientsmentioning
confidence: 99%
“…In the VANISH trial, a trend towards a 34% relative risk reduction of ES recurrences was observed among 132 patients treated by CA, in comparison with 127 patients who were conservatively managed. 39 We recently reported on the long-term outcomes of a large series of 267 patients presenting with ES undergoing CA. The acute elimination of all inducible VTs was achieved in 73% of the cases, with a 54% VT-free survival and a 93% ES-free survival rate at five years' follow-up.…”
Section: Electrical Storm In Icd Patientsmentioning
confidence: 99%
“…Nedavno objavljeno istraživanje VANISH bolesnike s ishemijskom kardiomiopatijom i ugrađe-nim defibrilatorom uz ventrikularnu tahikardiju koja ne reagira na lijekove randomiziralo je u skupinu onih s kateterskom ablacijom VT-a i nastavkom osnovne antiaritmične terapije nasuprot onima s postupnim pojačanjem antiaritmične terapije. 32 Finally, a very recent FDA analysis in 52 240 dabigatranand 66 651 rivaroxaban-treated elderly (≥ 65 years). Medicare patients revealed a trend for lower risk of thromboembolic stroke with rivaroxaban compared with dabigatran (HR, 0.81; 95% CI, 0.65-1.01; P = 0.07).…”
Section: Ventrikularne Aritmije I Iznenadna Srča-na Smrtunclassified
“…The recently published VANISH trial randomized patients with drug refractory ventricular tachycardia in the setting of ischemic cardiomyopathy and defibrillator protection to VT catheter ablation with continuation of baseline antiarrhythmic medications vs. escalated antiarrhythmic drug therapy. 32 In the latter group, amiodarone was initiated if another drug had been used previously. The dose of amiodarone was increased up to 300 mg/day and mexiletine was added thereafter, if clinically required.…”
Section: Ventricular Arrhythmias and Sudden Cardiac Deathmentioning
confidence: 99%
“…Previous studies provided evidence for reduced rates of implantable cardioverter‐defibrillator (ICD) shocks and prevention of electrical storm in patients after CA of VT as compared with medical treatment 2, 3. However, complication rates of CA are not negligible and include major complications such as myocardial rupture, coronary artery damage, and embolic stroke 1.…”
Section: Introductionmentioning
confidence: 99%